Permasalahan Etika Profesi Hakim Konstitusi dalam Putusan Nomor 90/PUU-XXI/2023: Refleksi atas Pengalaman yang Meruntuhkan Kepercayaan Masyaraka - Raafid Febriansyah (Esensi Hukum, 2025)
The third amendment to the Indonesian Constitution established the Constitutional Court (MK) to refine democratic and modern governance through a system of checks and balances. Pursuant to Article 24C Paragraph (1), MK's primary authority is to conduct judicial review of laws against the constitution. In 2023, MK faced a severe crisis following Decision No. 90/PUU-XXI/2023, which enabled the son of Indonesia’s seventh president to contest the 2024 General Election. This decision severely eroded public trust and led to the reporting of nine constitutional judges to the Constitutional Court’s Honorary Council (MKMK). Consequently, this article examines how Decision No. 90/PUU-XXI/2023 undermined public confidence and analyzes the ethical violations committed by the justices. This normative legal study employs case, statutory, and conceptual approaches. It utilizes secondary data from primary and secondary legal sources, analyzed through descriptive qualitative techniques. The findings indicate that Decision No. 90/PUU-XXI/2023, concerning the age limit for presidential and vice-presidential candidates, was riddled with irregularities and a disregard for independence and impartiality. Furthermore, the MKMK ruling confirmed that the panel violated the code of ethics; the most severe violation was committed by the Chief Justice, while the other eight justices committed minor infractions. As a preventive measure, it is imperative to reformulate the requirements for constitutional judge candidates alongside the procedures for their selection, election, and nomination